1997
DOI: 10.2190/fdpe-vvg2-vntr-n2dk
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi Chuan, an Alternative Form of Exercise for Health Promotion and Disease Prevention for Older Adults in the Community

Abstract: Thirty-six men and women age fifty or older participated in a study to examine the health effects of Tai Chi Chuan on older adults in a community setting. Participants in the experimental group (n = 23) received thirty-two one-hour sessions of Tai Chi Chuan instruction in sixteen weeks. Health effects were determined by measuring heart rate, blood pressure, muscle tension, anxiety, and flexibility. Results of data analysis indicated participants received training in Tai Chi Chuan had a greater improvement in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 5 publications
2
28
0
Order By: Relevance
“…Previous research has found that participation in both LIE and TC programs has resulted in decreased depressive symptoms (Chen & Sun, 1997;Moore & Brodsgaard, 1999;O'Connor et al, 1993;Singh et al, 1997). Many of these intervention studies lasted longer than 12 weeks; hence, consistent with our trend data, a statistical reduction in depressive symptoms is likely to be attainable if the duration of the intervention is extended.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Previous research has found that participation in both LIE and TC programs has resulted in decreased depressive symptoms (Chen & Sun, 1997;Moore & Brodsgaard, 1999;O'Connor et al, 1993;Singh et al, 1997). Many of these intervention studies lasted longer than 12 weeks; hence, consistent with our trend data, a statistical reduction in depressive symptoms is likely to be attainable if the duration of the intervention is extended.…”
Section: Discussionsupporting
confidence: 82%
“…Research consistently finds that TC has beneficial effects on cardiovascular function (Lan, Lai, Chen, & Wong, 1998;Young, Appel, Jee, & Miller, 1999), aerobic capacity (Taylor-Piliae & Froelicher, 2004), strength and flexibility (Lan et al, 1998;Lan, Chen, Lai, & Wong, 1999), sleep abilities (Li, Harmer, Fisher, & McAuley, 2004), balance and falls (Hain, Fuller, Weil, & Kotsias, 1999;Li et al, 2004;Thornton, Sykes, & Tang, 2004;Wolf et al, 1996;Wu, 2002), and blood pressure (Thornton et al, 2004). It also has positive effects on psychological well-being, resulting in improvements to self-esteem (Kutner, Barnhart, Wolf, McNeely, & Xu, 1997;Li, Harmer, Chaumeton, Duncan, & Duncan, 2002) and reduced anxiety, depression, and mood disturbance (Brown et al, 1995;Chen & Sun, 1997;Sandlund & Norlander, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies investigated traditional modes of exercise, to which patients often have difficulty adhering/complying. A form of exercise that may be particularly appropriate for breast cancer survivors is the practice of Tai Chi Chuan (TCC), which is rapidly gaining popularity in the United States [10]. It is an easily modifiable, low-to-moderate intensity form of physical exercise with psychological, physiological, and sociological benefits [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with such disorders frequently benefit from Tai Chi, as do elderly subjects with enhanced risk of falls and fractures23 . Tai Chi has also been found beneficial for several neurological 1, 12, 49, 68 , psychological 59 and cardiovascular conditions 65 .The modes of action of Tai Chi are not understood completely, they might include general effects due to exercise such as increased flexibility and mobility of structures; improved muscle strength and endurance, increased tensile strength of ligaments and capsules; increased cardiovascular function, reduced stress, anxiety and depression; and changes in health beliefs and health related locus of control 33 .Tai Chi in particular may act via improved postural control as indicated by increases in balance and reduced falls8,25, 46, 50, 64 . Specific mechanisms of postural control relevant to neck pain may be better muscle tone due to increased muscle strength28,30,36 and better kinesthetic control due to improved interoceptive or proprioceptive awareness 43 .…”
mentioning
confidence: 99%